2009
DOI: 10.1128/aem.01721-08
|View full text |Cite
|
Sign up to set email alerts
|

Intraspecies Genomic Diversity and Natural Population Structure of the Meat-Borne Lactic Acid Bacterium Lactobacillus sakei

Abstract: Lactobacillus sakei is a food-borne bacterium naturally found in meat and fish products. A study was performed to examine the intraspecies diversity among 73 isolates sourced from laboratory collections in several different countries. Pulsed-field gel electrophoresis analysis demonstrated a 25% variation in genome size between isolates, ranging from 1,815 kb to 2,310 kb. The relatedness between isolates was then determined using a PCR-based method that detects the possession of 60 chromosomal genes belonging t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
69
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(76 citation statements)
references
References 43 publications
5
69
1
Order By: Relevance
“…We then compared their genome sizes and organizations. PFGE analysis showed that L. sakei FLEC01 harbored seven rrn operons distributed on the chromosome, as previously observed for L. sakei (11,20,32). The genome size of L. sakei FLEC01 was evaluated to be 1,966 Ϯ 5 kb, thus, comparable to those of L. sakei 23K (1,885 kb) (20) and LTH5590 (1,915 Ϯ 22 kb) (11).…”
Section: Resultsmentioning
confidence: 58%
See 1 more Smart Citation
“…We then compared their genome sizes and organizations. PFGE analysis showed that L. sakei FLEC01 harbored seven rrn operons distributed on the chromosome, as previously observed for L. sakei (11,20,32). The genome size of L. sakei FLEC01 was evaluated to be 1,966 Ϯ 5 kb, thus, comparable to those of L. sakei 23K (1,885 kb) (20) and LTH5590 (1,915 Ϯ 22 kb) (11).…”
Section: Resultsmentioning
confidence: 58%
“…sakei shows high degrees of phenotypic and genomic diversity (11)(12)(13) that may explain the difficult detection and misidentification of it in the past. For instance, although the human gut microbiota has been intensively investigated by different microbial and molecular methods for many years, the presence of L. sakei in the feces of healthy humans was reported only recently (16,17,26,39).…”
mentioning
confidence: 99%
“…It has already been shown that pathways responsible for biogenic amine production are strain specific, with horizontal gene transfer being the mechanism responsible for this strain variation (8). Although extensive intraspecies genomic variability within L. sakei has been shown before (3,24), its occurrence solely in meat isolates may suggest a putative role of the AgDI pathway in meat adaptation. The two L. sakei strains with an operational AgDI pathway were able to produce the biogenic amine putrescine from agmatine through the AgDI pathway, thereby producing ammonia toward acid stress and extra ATP to improve competitiveness.…”
Section: Discussionmentioning
confidence: 99%
“…25) Previous study of the C. albicans isolate ATCC10231 identified 42 variable genes, including 5 amplified, and 37 absent/divergent genes, as compared with SC5314.…”
Section: Discussionmentioning
confidence: 99%